Food and Faith : a theology of eating - Wirzba, Norman (New York : Cambridge University Press, 2011)
"This book provides a comprehensive theological framework for assessing eating's significance, demonstrating that eating is of profound economic, moral, and theological significance"--
1. Thinking theologically about food -- 2. The 'roots' of eating: our life together in gardens -- 3. Eating in exile: dysfunction in the world of food -- 4. Life through death: sacrificial eating -- 5. Eucharistic table manners: eating toward communion -- 6. Saying grace -- 7. Eating in Heaven?: consummating communion.
Includes bibliographical references and indexes.
Keywords: Dinners and dining -- Religious aspects -- Christianity; Food -- Religious aspects -- Christianity; Food habits